Integrated Nutrient Management for Potatomungbean- T.Aman Rice Cropping Pattern Under Level Barind Agroecological Zone (Bangladesh Journal of Agricultural Research, 2012)
A field experiment was conducted at the Multiplication Testing Site (MLT),  Joypurhat Sadar upazila with Potato- Mugnbean T. Aman rice cropping pattern during November/2007 to November/2008 to verify different nutrient management approaches and to determine the economic dose of fertilizer for the said cropping pattern. The experiment was designed with five treatments for whole of the cropping pattern in a randomized complete block design with six replications. The treatments were, soil test based fertilizer dose for moderate yield goal, soil test based fertilizer dose for high yield goal, integrated plant nutrient management, farmers practice, and control. Cowdung was applied at the first crop potato only in the cropping sequence. The varieties for potato, mungbean and T. Aman rice were Diamant, BARI Mung-6, and BR11, respectively. The results demonstrated that the tuber yield of potato, seed yield  of mungbean, and grain yield of T. Aman rice were significantly influenced by the different treatments. The highest tuber yield (25.01 t/ha) was obtained from integrated plant nutrient management treatment. In mungbean, the highest seed yield (1384 kg/ha) was also recorded from NPKS for high yield goal with residual cowdung treatment. The results of NPKS application for high yield goal with residual cowdung had a positive effect on seed yield of mungbean. Grain and straw yields of T. Aaman rice were also significantly influenced by different treatments. The highest grain yield (5.68 t/ha) and straw yield (5.82 t/ha) were also observed in NPKS for high yield goal with residual cowdung treatment.  The results also indicated that the residual cowdung had a positive effect on grain and straw yields of T. Aman rice. Cost and return analysis of different nutrient management packages for the whole cropping pattern showed that the highest marginal benefit cost ratio (8.64), gross return (Tk. 3,79,960/ha) and gross margin (Tk. 3,43,360/ha) were obtained from integrated plant nutrient management treatment and the lowest from soil test based fertilizers for moderate yield goal treatment. So, considering crop productivity, economic return, and soil fertility, integrated plant nutrient management for high yield goal with 5 t/ha cowdung could be recommended for the Potato-Mungbean-T Aman rice cropping pattern at Joypurhat and similar soils of Level Barind agroecological zone for sustainable higher yield DOI: http://dx.doi.org/10.3329/bjar.v36i4.11761 Bangladesh J. Agril. Res. 36(4): 711-722, December 2011